2018
DOI: 10.2147/ccid.s158428
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a pseudo-ceramide and eucalyptus extract containing lotion on dry scalp skin

Abstract: ObjectiveDry and scaly conditions on the scalp are often observed in patients with atopic dermatitis, seborrheic dermatitis and/or pityriasis capitis. Those scalp lesions often exhibit low barrier function and reduced ceramide levels. Therefore, a clinical study was conducted to evaluate the efficacy of topical application of a pseudo-ceramide and eucalyptus extract-containing lotion on the scalps of patients with skin diseases.MethodsThirty-four subjects participated in this study (atopic dermatitis: 19 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“… 17 In addition, a recent study investigating a emulsion containing pseudo-ceramide and eucalyptus extract showed effectively improved dry and scaly scalp as well as the quality of life of 34 participants with different skin conditions (atopic dermatitis, seborrheic dermatitis, pityriasis capitis). 18 …”
Section: Discussionmentioning
confidence: 99%
“… 17 In addition, a recent study investigating a emulsion containing pseudo-ceramide and eucalyptus extract showed effectively improved dry and scaly scalp as well as the quality of life of 34 participants with different skin conditions (atopic dermatitis, seborrheic dermatitis, pityriasis capitis). 18 …”
Section: Discussionmentioning
confidence: 99%
“…Especially, scaling, erythema, and itching were significantly improved. The skin barrier function of the scalp was greatly improved [36]. Although this study was performed on patients with certain skin disorders, its results are also of value in the general population with weak scalp skin barriers.…”
Section: Scalp Barrier Functionmentioning
confidence: 96%
“…Показано, что экзогенные компоненты ЛТ проникают через роговой слой в клетки зернистого слоя эпидермиса; проходят через эндоплазматический ретикулум в сеть аппарата Гольджи, где формируются ЛТ. Показано, что использование увлажняющих препаратов замедляет прогрессию АтД и снижает тяжесть заболевания [30,31]. K. Mori и соавт.…”
Section: терапия кожи увлажняющими средствамиunclassified
“…Авторы показали, что в сухой летний период использование геля значительно улучшало состояние кожи, снижало покраснение, зуд, улучшало самочувствие больных по сравнению с больными, не использовавшими гель. Аналогичные данные были получены у больных себорейным дерматитом [31]. Этот же состав увлажняющего средства в сочетании с умеренной очисткой лица оказывал достоверный протективный эффект при акне средней тяжести у подростков с сухой и чувствительной кожей [32].…”
Section: терапия кожи увлажняющими средствамиunclassified